(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to identify occupational hazards and their impact on workers in dental clinics. The study sample consisted of (166) participants, and the descriptive-analytical method was adopted. A questionnaire was used to collect data from the study sample. The study reached the following results: -The level of occupational hazards to which workers in dental clinics in the Abu Salim area are exposed was found to be moderate. -The level of occupational safety procedures in dental clinics in the Abu Salim area was found to be high. -There were statistically significant differences at the (0.05) level in the impact of occupational hazards on workers in dental clinics in Abu Salim in its two dimensions (occupational hazards – occupational safety procedures) according to gender, in favor of males. -There were statistically significant differences at the (0.05) level in the impact of occupational hazards on workers in dental clinics in Abu Salim in its two dimensions (occupational hazards – occupational safety procedures) according to years of experience, in favor of those with (10 years or more) of experience. -There were statistically significant differences at the (0.05) level in the impact of occupational hazards on workers in dental clinics in Abu Salim in its two dimensions (occupational hazards – occupational safety procedures) according to training courses, in favor of those who received training.